The effects of saffron supplementation on cardiovascular risk factors in adults: A systematic review and dose-response meta-analysis - Zamani, Mohammad; Zarei, Mahtab; Nikbaf-Shandiz, Mahlagha; Gholami, Fatemeh; Hosseini, Amir Mehdi; Nadery, Maryam; Shiraseb, Farideh; Asbaghi, Omid (Frontiers in Nutrition, 2022)
Cardiovascular disease (CVD) is one of the leading causes of death and disability in the world and is estimated to involve more people in the next years. It is said that alternative remedies such as herbs can be used to manage the complications of this disease. For this reason, we aimed to conduct this meta-analysis to systematically assess and summarize the effects of saffron supplementation as an important herb on cardiovascular risk factors in adults. A systematic search was done in PubMed, Scopus, and Web of Science to find eligible articles up to September 2022. Randomized controlled trials (RCTs) that evaluated the effects of saffron on lipid profiles, glycemic control, blood pressure, anthropometric measures, and inflammatory markers were included. In the meta-analysis, 32 studies were taken into account (n=1674). Consumption of saffron significantly decreased triglyceride (TG) (WMD= -8.81 mg/dl, 95%CI: -14.33, -3.28; P=0.002), total cholesterol (TC) (WMD= -6.87 mg/dl, 95%CI: -11.19, -2.56; P=0.002), low density lipoprotein (LDL) (WMD= -6.71 mg/dl, 95%CI: -10.51, -2.91; P=0.001), (P=0.660), fasting blood glucose (FBG) level (WMD= -7.59 mg/dl, 95%CI: -11.88, -3.30; P=0.001), HbA1c (WMD= -0.18 %, 95%CI: -0.21, -0.07; P<0.001), homeostasis model assessment-insulin resistance (HOMA-IR) (WMD= -0.49, 95%CI: -0.89, -0.09; P=0.016), systolic blood pressure (SBP) (WMD= -3.42 mmHg, 95%CI: -5.80, -1.04; P=0.005), tumor necrosis factor α (TNF-α) (WMD= -2.54 pg/ml, 95%CI: -4.43, -0.65; P=0.008), waist circumference (WC) (WMD= -1.50 cm; 95%CI: -2.83, -0.18; P=0.026), malondialdehyde (MDA) (WMD= -1.50 uM/L, 95%CI: -2.42, -0.57; P=0.001), and alanine transferase (ALT) (WMD= -2.16 U/L, 95%CI: -4.10, -0.23; P=0.028). Also, we observed that saffron had an increasing effect on total antioxidant capacity (TAC) (WMD= 0.07 mM/L, 95%CI: 0.01, 0.13; P=0.032). There was linear regression between FBG and the duration of saffron intake. Additionally, the nonlinear dose-response analysis has shown a significant association of saffron intervention with HDL (P=0.049), HOMA-IR (P=0.002), weight (P=0.036), ALP (P=0.016), FBG (P=0.011), HbA1c (P=0.002), and TNF-α (P=0.042). A non-linear association between the length of the intervention and the level of HDL and DBP was also found. That seems saffron could effectively improve TG, TC, LDL, FBG, HbA1c, HOMA-IR, SBP, CRP, TNF-α, WC, MDA, TAC, and ALT.